2023
DOI: 10.2500/aap.2023.44.220091
|View full text |Cite
|
Sign up to set email alerts
|

SNOT-22 scores after 6 months of aspirin therapy are predictive of long-term quality of life in AERD

Abstract: Background: Aspirin exacerbated respiratory disease (AERD) is an inflammatory condition that consists of eosinophilic asthma, chronic rhinosinusitis with nasal polyps, and respiratory reactions to cyclooxygenase-1 inhibitors. Aspirin therapy after aspirin desensitization (ATAD) is the most extensively studied treatment paradigm for AERD. Objective: The objective was to identify which time point of ATAD was most predictive of long-term outcomes as measured by the 22-item Sino-Nasal Outcome Test (SNOT-22). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this regard, a total score of 20 at the SNOT-22 has been defined to be the threshold to distinguish responders (SNOT-22 < 20) from non-responders (SNOT-22 ≥ 20) [24]. Moreover, a recent study from Tripathi et al [25] found that the SNOT-22 score obtained at 6 months post-desensitisation had the greatest predictive value for long-term outcomes at 24 months post-desensitisation, with an OR of 16.5, proposing a 6-month time point of ATAD as a predictor for long-term success. In our practice, we tend to consider a patient a good responder to the treatment when their SNOT-22 score significantly improves from baseline (SNOT-22 before treatment).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a total score of 20 at the SNOT-22 has been defined to be the threshold to distinguish responders (SNOT-22 < 20) from non-responders (SNOT-22 ≥ 20) [24]. Moreover, a recent study from Tripathi et al [25] found that the SNOT-22 score obtained at 6 months post-desensitisation had the greatest predictive value for long-term outcomes at 24 months post-desensitisation, with an OR of 16.5, proposing a 6-month time point of ATAD as a predictor for long-term success. In our practice, we tend to consider a patient a good responder to the treatment when their SNOT-22 score significantly improves from baseline (SNOT-22 before treatment).…”
Section: Discussionmentioning
confidence: 99%